Survei Tingkat Kebugaran Jasmani Dan Pemahaman Law Of The Game Wasit Askab Magelang 2020 (Universitas Negeri Semarang, 2021)
The background of this research is that the performance of referees cannot be separated from physical fitness and understanding of LOTG. Law Of The Game or LOTG is the main obligation for a referee. The referee is someone who has the authority to lead the course of a soccer match. The referee must act fairly, neutral and firmly when leading the course of the match so that there is no clash. The role of LOTG is very important, to organize a sporting match. The referee's own understanding of LOTG has many determining factors, one of which is physical fitness. And the purpose of this study was to determine the relationship between physical fitness and understanding of LOTG (Law Of The Game) Wasit Askab Magelang 2020. This research is a quantitative research, the method used to collect data is the survey method. The subjects in this study were 24 ASKAB Magelang Referees. The data analysis technique used was correlation analysis with a significant level of 5%. The results showed that the physical fitness of the Magelang District Referee (ASKAB Magelang Referee) was in the fair category, the understanding of Law Of The Game Referee in Magelang Regency (Wasit ASKAB Magelang) was mostly good. The results of the variable coefficient of the relationship between physical fitness and understanding of the Law of the Game of referees in Magelang Regency, obtained the value of rcount = 0.497> r table (0.05) (23) = 0.396, thus it was concluded that there was a positive relationship between physical fitness and understanding of the Law Of The Game referees in the district. magelang (ASKAB Magelang Referee). The conclusion of this research is that the referee's physical fitness is very important to support the understanding of LOTG (Law Of The Game). Through the results of this research it can be used as a longitudinal study which allows the evaluation of developments in soccer referees around the world.